Determining the Surface Area of a Tube Using the Discovery Learning Model at SMP Negeri 5 Sinunukan - Torang Siregar; Almira Amir; Lelya Hilda; Suparni; Anita Adinda (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2023)
Teachers almost never carry out learning that is oriented towards higher order thinking skills (HOTS). The author also rarely uses learning media. As a result, the learning atmosphere in the classroom is stiff and the children don't look cheerful. .based on the results of interviews with several students, information was obtained that (a) students were lazy to attend lessons that were mostly carried out by the teacher by means of lectures (b) apart from lectures, the method that was always used by the teacher was assignments or homework (PR). Some students claim to be bored with tasks that are only theoretical. To face the Industrial Revolution 4.0 era, students must be equipped with higher-order thinking skills. One of the HOTS-oriented learning models and suggested in the implementation of the 2013 Curriculum is the Discovery Learning learning model. Discovery learning is a learning process that occurs when students are not presented with information directly but students are required to organize their understanding of that information independently. After carrying out the mathematics learning model of Discovery Learning, the authors found that the learning processes and results of students increased. Better than previous studies. When the Discovery Learning model was applied to other VIII graders, it turned out that the students' learning processes and outcomes were just as good. Discovery Learning learning practices that work well, the authors conclude as a HOTS-oriented learning best practice with the Discovery Learning model.